Biến đổi thành phân thức ĐS: `( 1 – 2/(x+1))/(1 – (x^2-2)/(x^2-1))`

Question

Biến đổi thành phân thức ĐS:
`( 1 – 2/(x+1))/(1 – (x^2-2)/(x^2-1))`

in progress 0
Kylie 2 tuần 2021-07-10T11:45:26+00:00 2 Answers 2 views 0

Answers ( )

    0
    2021-07-10T11:46:37+00:00

    Đáp án+Giải thích các bước giải:

    ĐKXĐ: `x\ne ±1`

     `(1-2/(x+1))/(1-(x^2-2)/(x^2-1))`

    `=(1-2/(x+1)):(1-(x^2-2)/(x^2-1))`

    `=(x+1-2)/(x+1):(x^2-1-x^2+2)/(x^2-1)`

    `=(x-1)/(x+1):1/(x^2-1)`

    `=(x-1)/(x+1).(x-1)(x+1)`

    `=(x-1)^2`

    0
    2021-07-10T11:46:44+00:00

    ĐKXĐ: \(x\ne ±1\)

    Đặt \(A=\dfrac{1-\dfrac{2}{x+1}}{1-\dfrac{x^2-2}{x^2-1}}\)

    \(1-\dfrac{2}{x+1}\\=\dfrac{x+1-2}{x+1}\\=\dfrac{x-1}{x+1}\)

    \(1-\dfrac{x^2-2}{x^2-1}\\=\dfrac{x^2-1-x^2+2}{x^2-1}\\=\dfrac{1}{x^2-1}\\=\dfrac{1}{(x-1)(x+1)}\)

    \(→A=\dfrac{\dfrac{x-1}{x+1}}{\dfrac{1}{(x-1)(x+1)}}\\=\dfrac{x-1}{x+1}:\dfrac{1}{(x-1)(x+1)}\\=\dfrac{x-1}{x+1}.(x-1)(x+1)\\=(x-1)^2\)

    Vậy với \(x\ne ±1\) thì \(\dfrac{1-\dfrac{2}{x+1}}{1-\dfrac{x^2-2}{x^2-1}}=(x-1)^2\)

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )